2002
DOI: 10.1002/hed.10057
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for positron emission tomography with 18F‐fluorodeoxyglucose in the initial staging of nodal negative oral and oropharyngeal squamous cell carcinoma

Abstract: PET with FDG turned out to have a poor sensitivity and specificity in revealing occult metastasis and has no role for the evaluation of otherwise clinically N0 necks. The failure to detect micrometastasis by PET is due to the technical limitations of resolution (4-5 mm). SLN biopsy, with END in cases of positive SLN, provides a highly accurate staging of N0 necks in oral and oropharyngeal carcinoma. Patients with negative SLN could be spared the risks and the morbidity of END.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(77 citation statements)
references
References 19 publications
4
70
1
2
Order By: Relevance
“…It is still a matter of controversy as to how FDG-PET/CT should be integrated into the staging algorithm of patients with HNSCC [24]. We use FDG-PET/CT in patients with suspected advanced primaries and/or metastases, and we recommend that it should be performed prior to panendoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…It is still a matter of controversy as to how FDG-PET/CT should be integrated into the staging algorithm of patients with HNSCC [24]. We use FDG-PET/CT in patients with suspected advanced primaries and/or metastases, and we recommend that it should be performed prior to panendoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study reinforce what was reported by Schoder et al in the clinically lymph nodal-negative neck (25). Despite a reasonably high overall accuracy, the clinical application of 18 F-FDG PET/CT may be limited by the suboptimal sensitivity for small metastases and the relatively high number of false-positive findings (28).…”
Section: Discussionmentioning
confidence: 99%
“…Studies applying a radiolabelled tracer with or without additional blue dye, however, were promising. The majority of the studies reported results favouring the sentinel lymph-node concept (Koch et al, 1998;Shoaib et al, 1999Shoaib et al, , 2001Alex et al, 2000;Zitsch et al, 2000;Mozzillo et al, 2001;Stoeckli et al, 2001Stoeckli et al, , 2002Barzan et al, 2002;Werner et al, 2002a, b). Groups who worked with blue dye report of an extravasation of the blue dye into the tissue (Pitman et al, 2002).…”
Section: Discussionmentioning
confidence: 99%